Effects on Lettuce Yield Parameters and Toxicological Safety Assessment of a Plant-Derived Formulation Based on Rosemary and Eucalyptus Essential Oils - Kapnisis, Konstantinos; Chrysargyris, Antonios; Prokopi, Marianna; Varda, Eleni; Kokkinidou, Despoina; Samourides, Andreas; Xylia, Panayiota; Onisiforou, Pavlina; Stavrinides, Menelaos; Tzortzakis, Nikos G.; Anayiotos, Andreas (My University, 2022)
Essential oils from medicinal and aromatic plants are increasingly recognized as a promising class of green molecules for use in crop production. In many cases, the beneficial aspects of a substance are not supported by sufficient toxicological safety testing, even though recent reports suggest that some compounds may be toxic to terrestrial or aquatic non-target species. It is, therefore, essential to investigate the possibility of adverse effects on non-target animals and humans exposed to these substances through the consumption of fruit and/or vegetables. The present study aims to examine the potential effects on yield and quality parameters and investigate the level of in vitro and in vivo toxicity of an Eco-product (EP) based on rosemary and eucalyptus essential oils, to provide a measure for safe use in the agricultural sector. The product was evaluated in lettuce crop production and indicated that one-time application of the EP formula increases yield, activating various secondary metabolism pathways of the plant to cope with oxidative stress. Cytotoxicity assays and in vivo acute oral and dermal toxicity studies suggest that the tested compound does not pose any significant health hazard, and the dissolved product can be classified in Category 5, according to the Globally Harmonized System of Classification and Labelling of Chemicals (GHS).
Keywords: cytotoxicity; acute oral and dermal toxicity; medicinal and aromatic plant; biostimulant; oxidative stress; toxicological safety